THE INFLUENCE OF PRICE PERCEPTION AND RISK PERCEPTION ON PURCHASE INTENTION AND PURCHASE DECISIONS OF CUSTOMS-PAID IPHONES IN PEKANBARU - Bayu Pramudia; Rahmat Setiawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of price perception and perceived risk on purchasing decisions of customs-paid iPhones, with purchase intention as a mediating variable in Pekanbaru. The study employs a quantitative approach using Structural Equation Modeling (SEM) with AMOS to examine the relationships among variables. The sample consists of 152 respondents selected through purposive sampling. The results indicate that price perception has a positive and significant effect on purchase intention, while purchase intention has a strong and significant influence on purchasing decisions. However, perceived risk does not show a significant effect on either purchase intention or purchasing decisions. Furthermore, purchase intention is proven to act as a mediating variable that strengthens the relationship between price perception and purchasing decisions. These findings suggest that consumers tend to evaluate premium products such as iPhones based on perceived value rather than solely on price affordability or risk considerations. Therefore, businesses should focus on strengthening value-based pricing strategies and enhancing consumer purchase intention to increase purchasing decisions.